Alu-Sc-mediated exonization generated a mitochondrial LKB1 gene variant found only in higher order primates - Ivan Tan; Sonia Chothani; Hong-Hwa Lim; Kong-Peng Lam (Scientific Reports)
Abstract The tumor suppressor LKB1/STK11 plays important roles in regulating cellular metabolism and stress responses and its mutations are associated with various cancers. We recently identified a novel exon 1b within intron 1 of human LKB1/STK11, which generates an alternatively spliced, mitochondria-targeting LKB1 isoform important for regulating mitochondrial oxidative stress. Here we examined the formation of this novel exon 1b and uncovered its relatively late emergence during evolution. Analyses of putative exon 1b genomic sequences within the primate superfamily indicated that the exonization of LKB1/STK11 exon 1b was mediated by the conserved retrotransposable element Alu-Sc. While putative exon 1b sequences are recognizable in most members of the primate family from New World Monkeys onwards, characteristically functional LKB1/STK11 exon 1b, with translation start and 5ʹ and 3ʹ splice sites, could only be found in greater apes and human, and interestingly, correlates with their increased body mass and longevity development.